Integrating Gaze Direction and Expression in Preferences for Attractive Faces - Jones, Benedict C.; DeBruine, Lisa M.; Little, Anthony C.; Conway, Claire A.; Feinberg, David R. (Psychological Science, 2006)
Few studies have investigated how physical and social facial cues are integrated in the formation of face preferences. Here we show that expression differentially qualifies the strength of attractiveness preferences for faces with direct and averted gaze. For judgments of faces with direct gaze, attractiveness preferences were stronger for smiling faces than for faces with neutral expressions. By contrast, for judgments of faces with averted gaze, attractiveness preferences were stronger for faces with neutral expressions than for smiling faces. Because expressions can differ in meaning depending on whether they are directed toward or away from oneself, it is only by integrating gaze direction, facial expression, and physical attractiveness that one can unambiguously identify the most attractive individuals who are likely to reciprocate one's own social interest.